Angular-Dependent EDMR Linewidth for Spin-Dependent Space-Charge-Limited Conduction in a Polycrystalline Pentacene - Fukuda, Kunito; Asakawa, Naoki (Frontiers in Materials, 2017)
Spin-dependent space charge limited carrier conduction in a Schottky barrier diode using polycrystalline p-type $π$-conjugated molecular pentacene is explored using multiple-frequency electrically detected magnetic resonance (EDMR) spectroscopy with a variable-angle configuration. The measured EDMR spectra are decomposed into two components derived respectively from mobile and trapped positive polarons. The linewidth of the EDMR signal for the trapped polarons increases with increasing resonance magnetic field for an in-plane configuration where the normal vector of the device substrate is perpendicular to the resonance magnetic field, while it is independent of the field for an out-of-plane configuration. This difference is consistent with the pentacene arrangement on the device substrate, where pentacene molecules exhibit a uniaxial orientation on the out-of-substrate plane. By contrast, the mobile polarons do not show anisotropic behavior with respect to the resonance magnetic field, indicating that the anisotropic effect is averaged out owing to carrier motion. These results suggest that the orientational arrangements of polycrystalline pentacene molecules in a nano thin film play a crucial role in spin-dependent electrical conduction.